Creatine monohydrate ingested daily compared to only on training days on body composition, muscle thickness, and strength after 12 weeks of resistance training: preliminary results - Ignacio Quiroz; Scott C. Forbes; Thomas Hayes; Felipe Bermúdez; Alan Szinavel; Cristian Campos; Paula Méndez; Francisco Pino de la Fuente; Claudio Pérez de Tudela; Álvaro Reyes; Bruno Ticozzi; Mauricio Jorquera; et al. (Journal of the International Society of Sports Nutrition)
Background Creatine monohydrate (Cr) supplementation in conjunction with resistance training is one of the most widely used strategies to increase lean tissue mass and muscle performance. However, whether the frequency of Cr ingestion (e.g. daily vs. only on training days) alters the efficacy of Cr supplementation remains to be elucidated. Therefore, the purpose was to investigate the effects of 12-weeks of resistance training with creatine taken either daily or taken only on training days on body composition, muscle thickness, and strength in healthy trained young men and women.Methods Preliminary data of an outgoing recruitment in six trained young adults (27 ± 3 y; n = 3 women; n = 3 men) were collected. Participants performed supervised resistance training (3 times per week) for 12 weeks. Participants were randomly assigned to receive either 5 g of Cr daily or 5 g only on training days. Resistance training sessions consisted of full-body routines, three sets of 8–12 repetitions, at 2–3 repetitions in reserve. A certified trainer supervised all sessions. Loads were adjusted every 2 weeks to maintain exercise intensity. Assessments of body composition were done by bioelectric impedance (InBody), muscle thickness measures at the vastus lateralis (VL), pectoralis major, biceps brachii, and triceps brachii were done via ultrasound, and muscle strength was determined via isometric mid-thigh pull (IMTP) (Hawkin Dynamics, USA) and isokinetic knee extension torques before and after 12-weeks of training.Results There were no significant changes over time or between groups for body fat % (Group 1: Pre: 17.3 ± 7.1%, Post: 19 ± 7.6%, p = 0.10; Group 2: Pre: 20.9 ± 13.3%, Post: 18.7 ± 12%, p = 0.60) or skeletal muscle mass (Group 1: Pre: 27.5 ± 8.6 kg, Post: 27.8 ± 9.1 kg, p = 0.59; Group 2: Pre: 28.6 ± 9.5 kg, Post: 29.4 ± 10.1, p = 0.21). There was a significant main effect of time for muscle thickness at the VL (Group 1: Pre: 2.31 ± 0.11 cm, Post: 2.62 ± 0.0 cm, p = 0.03; Group 2: Pre: 2.5 ± 0.11 cm, Post: 2.8 ± 0.25 cm, p = 0.03), pectoralis major (Group 1: Pre: 1.28 ± 0.72 cm, Post: 1.52 ± 0.62, p = 0.04; Group 2: Pre: 1.3 ± 0.16 cm, Post: 1.5 ± 0.28 cm, p = 0.03) and triceps brachii (Group 1: Pre: 0.89 ± 0.72 cm, Post: 1.31 ± 0.82 cm, p = 0.009; Group 2: Pre: 1.5 ± 0.70 cm, Post: 2.0 ± 0.69 cm, p = 0.004), while no time or group differences where observed for the biceps brachii. There were also no differences over time or between groups for the IMTP (Group 1: Pre: 1794 ± 447.5N, Post: 1886 ± 443.6N, p = 0.10; Group 2: Pre: 2011 ± 511.4N, Post: 2035 ± 568.5N, p = 0.62). The left leg isokinetic knee extension torque significantly increased only in group 1 (Group 1: Pre: 133.3 ± 38.6 Nm, Post: 175.7 ± 32.6 Nm, p = 0.02; Group 2: Pre: 152.3 ± 35.6 Nm, Post: 149 ± 568.5 Nm, p = 0.84), while there were no changes on the right leg (Group 1 p = 0.09 and Group 2 p = 0.79).Conclusion Overall, there were similar responses following 12 weeks of resistance training between creatine ingestion strategies (daily vs. only on training days). However, caution is warranted based on the small sample size and low statistical power.